MicroRNA-4516 in extracellular vesicles-derived mesenchymal stem cells suppressed integrin αV-mediated lung fibrosis - Issei Sumiyoshi; Shinsaku Togo; Junko Watanabe; Izumi Kaneko; Seiji Uzu; Toshiya Yonekura; Tomoya Komatsu; Motoyasu Kato; Shun Nakazawa; Hiroaki Motomura; Yusuke Ochi; Kotaro Kadoya; et al. (Stem Cell Research & Therapy)
Abstract Background Idiopathic pulmonary fibrosis (IPF) is characterized by the recruitment of lung fibroblasts to sites within the lung interstitium, along with the differentiation of myofibroblasts induced by transforming growth factor (TGF)-β1, a mediator of fibrosis, which, in turn, leads to accelerated contractile lung fibrotic processes with excessive extracellular matrix (ECM) deposition. Extracellular vesicles (EVs) are small particles released by cells that contain physiologically active substances, including messenger RNAs, microRNAs (miRNAs), and proteins. Although EVs derived from mesenchymal stem cells (MSCs) are expected to be a promising drug for various intractable diseases, including IPF, the underlying mechanisms remain elusive. In this study, we aimed to elucidate the mechanisms underlying the effect of MSC-EVs on lung fibroblast-mediated antifibrotic processes. Methods The ability of TGF-β1-stimulated lung fibroblasts to migrate toward fibronectin and to contract three-dimensional type I collagen gels was evaluated. Using a miRNA array, we aimed to identify miRNAs associated with fibrotic mechanisms in MSC-EVs. Furthermore, the effects of MSC-EVs were analyzed in a mouse model of bleomycin (BLM)-induced lung fibrosis, including the resulting histopathology, degree of fibrosis, and downstream signaling pathways. Results Administration of MSC-EVs resulted in significant suppression of TGF-β1-stimulated collagen gel contraction, migration, and expression of α-smooth muscle actin and ECM. Upon treatment with MSC-EVs, lung fibroblasts derived from fibrotic lungs showed greater inhibition of responses than normal lung fibroblasts. These effects were mediated via the integrin αV-mediated focal adhesion kinase signaling through the MAPK pathway, including JNK, p38MAPK, and/or ERK1/2 signaling. miR-4516, identified in MSC-EVs in human lung fibroblasts, recapitulated these effects. Administration of MSC-EVs resulted in the significant accumulation and attenuation of BLM-induced fibrotic lung tissue, along with the reduced expression of integrin αV in the lung interstitium. Conclusion Collectively, the findings of this study indicate that MSC-EVs may represent a promising novel therapeutic strategy to address the pulmonary fibroblast-mediated mechanisms of lung fibrosis.